THE FOLKLORE AS A PHYSICAL EDUCATION INSTRUMENT RESCUING BRAZILIAN CULTURE ON ELEMENTARY AND HIGH SCHOOL (Fiep Bulletin - online, 2014)
We found on the National Curricular Parameters (PCN's) the elements for students social-culture education and due to it we elucidate importance of the physical education professional on school. On school environment, the attention dedicated to culture and its ramifications is reaffirmed by the PCN's on the different curricular disciplines, including physical education. This way, the teacher needs to use elements  in order to execute interventions about his cultural boarding schedule.  Through bibliographical research, it was possible to realize the relation between culture and physical education with folklore as instrument on Brazilian cultural rescue for elementary and high school. Many researches made about this issue, lead us to believe that folklore is a relevant  instrument on physical education presenting as goal the rescue of Brazilian culture on school environment and then the student social-cultural education once it shows culture ramifications that  influence the person corporal conscience .
Keywords: folklore; culture; physical education